The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1177/1479973119858961
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic pulmonary fibrosis: Educational needs of health-care providers, patients, and caregivers

Abstract: Idiopathic pulmonary fibrosis (IPF) is a progressive disease associated with poor quality of life. Debilitating symptoms and the reality of shortened survival impact patients’ physical and emotional well-being and constrain the lives of patients’ caregivers. This study assessed the informational needs of medical providers who care for patients with IPF, IPF patients themselves, and their caregivers. Tailored surveys were sent electronically to providers, patients with IPF, and caregivers of patients with IPF c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 18 publications
2
30
0
Order By: Relevance
“…15 studies used semi-structured and in-depth interviews (43%), 11 administered questionnaires [7,14,17,24,33,[37][38][39][40][41][42], five used focus groups [13,20,21,23,27], three used a combination of methods [26,31,35], and one used narrative data from websites [12]. 23 (65%) studies used a qualitative data analysis method.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…15 studies used semi-structured and in-depth interviews (43%), 11 administered questionnaires [7,14,17,24,33,[37][38][39][40][41][42], five used focus groups [13,20,21,23,27], three used a combination of methods [26,31,35], and one used narrative data from websites [12]. 23 (65%) studies used a qualitative data analysis method.…”
Section: Resultsmentioning
confidence: 99%
“…Quantitative methods were used to report findings regarding disease management [7,38,39], patient education and support [17,24], patient expectations of care [41], quality of life [26,38,41] and anxiety [24]. Six studies were conducted using mixed methods [26,31,33,35,37,42]. Meta-analysis was not possible as the number of quantitative studies was small and the data heterogeneous.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest ranked educational need was on how to reach the diagnosis of IPF. Participants expressed the need for printed or online educational materials, and support staff for educating patients [ 34 ]. In a European-wide survey about gaps in care for pulmonary fibrosis, distributed through the ERN-LUNG network, less than half (39%) of participating healthcare professionals responded that they received education on how to communicate information on diagnosis and treatment plan with their patients [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with ILD reported different needs than patients with COPD. A survey in the USA found that patients ranked disease progression and what to expect, as well as IPF drug therapy, followed by IPF diagnosis as the main educational needs [ 34 ]. Literature on how to provide information and education to patients with rare lung diseases is scarce.…”
Section: Introductionmentioning
confidence: 99%